Shifting Temporal Planes: Affective Temporality in Immersive Audio-Photographic Installation art (International Journal on Stereo & Immersive Media, 2017)
SHIFTING TEMPORAL PLANES: AFFECTIVE TEMPORALITY IN IMMERSIVE AUDIOPHOTOGRAPHIC INSTALLATION ART   HALI SANTAMAS - Independent researcher, UK